Peer-Supported Practice Strategy in Overcoming Public Speaking Anxiety (PSA) among Students - Solihati, Tri Agustini Solihati; Mulyanti, Wida; Julistiana, Risma; Eko, Eko; Santosa, Muhammad Alfirizky; Samrotussani, Yusti (LPPM Universitas Pancasakti Tegal, 2025)
This study aims to examine the effectiveness of the Peer-Supported Practice Strategy (PSPS) in reducing PSA among university students enrolled in a Public Speaking class, as well as to explore how students with different speaking proficiency levels respond to the strategy. Using a mixed-method approach, the research employed a quasi-experimental one-group pretest–posttest design complemented by qualitative interviews. Thirty students participated in the study and completed a 12-item PSA questionnaire administered before and after the PSPS intervention. Quantitative data were analyzed using descriptive statistics, paired sample t-tests, and independent t-tests. The results showed a notable decrease in PSA, with mean scores dropping from 45.93 (pretest) to 39.28 (posttest). The paired sample t-test revealed a statistically significant reduction, indicating that PSPS effectively lowered students’ anxiety levels. Furthermore, the independent t-test showed that both beginner and advanced proficiency groups benefited from the strategy, although beginners experienced a greater reduction. Qualitative interview findings further supported the quantitative results. Students reported feeling more comfortable, less fearful of making mistakes, and more confident when speaking with peers who offered supportive feedback. They emphasized that practicing in a non-judgmental environment, receiving constructive correction, and engaging in repeated speaking tasks helped them manage anxiety more effectively. Overall, the integration of peer support within structured speaking practice proved beneficial in reducing anxiety and increasing students’ speaking confidence. The findings suggest that PSPS can serve as an effective pedagogical approach for public speaking courses, particularly for students who struggle with communication apprehension.